Stress-strain behavior, cracking and bearing strength of foam concrete slabs punched through ricid stamps - Verba, V.; Demchyna, K. (Видавництво Львівської політехніки, 2014)
The article is devoted to the stress-strain behavior, cracking and bearing strength of plain and reinforced non-autoclaved foam concrete slab spunched through rigid stamp. Experimental researches were held on slabs freely supported along the contour. Authors made an effort to determine the level of loading that corresponded the start of cracking and it was set at the level of 0,6 N cr . There was also evaluated the ultimate tensility of foam concrete. Досліджено несучу здатність, тріщиноутворення та деформативність армованих та неармованих плит, виготовлених із безавтоклавного пінобетону, які випробовувалися на продавлювання жорстким штампом. Експериментальні дослідження проводилися на вільно опертих по контуру плитах. Автори зробили спробу встановити навантаження початку тріщиноутворення у пінобетонних плитах, які продавлюються, що становило ≈ 0,6 від N cr , та граничну розтягуваність пінобетону.
Keywords: foam concrete; punching; ultimate tensility; bearing strength; cracking; пінобетон; продавлювання; гранична розтягуваність; міцність на зминання; тріщиноутворення